Pseudo Almost Automorphic Solutions for Non-Autonomous Stochastic Differential Equations with Exponential Dichotomy (Communications in Mathematical Research, 2021)
In this paper, we consider the existence and uniqueness of the solutionswhich are pseudo almost automorphic in distribution for a class of non-autonomousstochastic differential equations in a Hilbert space. In conclusion, we use the Banachcontraction mapping principle and exponential dichotomy property to obtain ourmain results.
Keywords: pseudo almost automorphy; exponential dichotomy; non-autonomous stochastic differential equation.